Genetic effects in children exposed in prenatal period to ionizing radiation after the chornobyl nuclear power plant accident - Stepanova, Ye.I.; Vdovenko, V.Yu.; Misharina, Zh.A.; Kolos, V.I.; Mischenko, L.P. (Experimental Oncology, 2016)
Aim: To study the genetic effects in children exposed to radiation in utero as a result of the Chornobyl nuclear power plant accident accounting the total radiation doses and equivalent radiation doses to the red bone marrow. Materials and Methods: Incidence of minor developmental anomalies was studied in children exposed to radiation in utero (study group) and in the control group (1144 subjects surveyed in total). Cytogenetic tests using the method of differential G-banding of chromosomes were conducted in 60 children of both study and control groups (10–12-year-olds) and repeatedly in 39 adolescents (15–17-year-olds). Results: A direct correlation was found between the number of minor developmental anomalies and fetal dose of radiation, and a reverse one with fetal gestational age at the time of radiation exposure. Incidence of chromosomal damage in somatic cells of 10–12-year-old children exposed prenatally was associated with radiation dose to the red bone marrow. The repeated testing has revealed that an increased level of chromosomal aberrations was preserved in a third of adolescents. Conclusion: The persons exposed to ionizing radiation at prenatal period should be attributed to the group of carcinogenic risk due to persisting increased levels of chromosome damage. This article is a part of a Special Issue entitled “The Chornobyl Nuclear Accident: Thirty Years After”.